Growth performance responses to increased tryptophan supplementation in growing barrows fed three different very low crude protein corn and soybean meal‐based diets fortified with essential amino acids. (13th August 2021) - Sato, Hiroyuki; Miura, Makoto; Fujieda, Takeshi; Taciak, Marcin; Kikusato, Motoi; Sato, Kan; Toyomizu, Masaaki
Abstract: Seventy‐five individually fed barrows averaging 35 kg were used in a series of three experiments for 6‐week growth assays (25 barrows each) to determine the effects of l ‐tryptophan (Trp) supplementation on growth performance and to establish the lower limits of dietary crude protein (CP) levels. Corn and soybean meal (SBM)‐based diets containing 9% (Experiment 1), 10% (Experiment 2), and 11% CP (Experiment 3) fortified with deficient essential amino acids (AAs) except Trp were used as basal diets for each experiment. The experimental diets were supplemented with 0.00%, 0.02%, 0.04%, or 0.06% Trp. A 16% CP corn–SBM‐based diet was set as a positive control in each experiment, and feed and water were provided ad libitum. Average daily gain and gain‐to‐feed ratio improved quadratically ( P < 0.05) as supplemented Trp increased in the 9% and 10% CP group, although these positive effects were not observed in the 11% CP group. Because the maximum performance parameters in 9%, 10%, and 11% CP groups were not different from that of the 16% CP positive control group, the marginally reduced level of dietary CP without growth performance being affected appears to be around 9% at most. A potential reduction of nitrogen intake was clearly indicated.